Informal workplaces and their comparative effects on the health of street vendors and home-based garment workers in Yangon, Myanmar: a qualitative study - Thant Ko Ko; Julia Dickson-Gomez; Gisèle Yasmeen; Wai Wai Han; Katherine Quinn; Kirsten Beyer; Laura Glasman (BMC, 2020)
Abstract Background Globally, two billion workers are employed informally but there is limited research on the relationship between informal work and health. Existing studies have focused on informality as an employment condition, with little emphasis on the diversity of physical and social contexts in which informal work takes place. The study considers the diversity of informal workplaces and explores the ways in which this diversity might influence health and well-being of two informal occupational groups in Yangon, the former capital of Myanmar. Methods We conducted 21 field observations and 47 semi-structured interviews with street vendors and home-based garment workers based in Yangon, Myanmar. A constant comparative method was used to identify and compare how the physical characteristics of their informal workplaces affect their health for these two informal subgroups. Results Although both street vendors and home-based garment workers work informally, their exposure to occupational health and income risks are specific to the physical features of their informal workplaces. Street vendors, who work in public spaces with minimal coverage, are more likely to experience the direct effects of outdoor pollution, inclement weather and ergonomic risks from lifting, carrying and transporting heavy merchandise while home-based garment workers, many of whom live and work in unsanitary housing and deprived neighborhoods, are more likely to experience pollution in or near their homes, and ergonomic risks from poor posture. Similarly, although both groups face safety challenges, street vendors face urban violence and abuse during their commute and at vending points whereas home-based garment workers felt unsafe in their home-based workplaces due to the presence of crime and violence in their neighborhoods. Conclusion While informal employment is universally characterized by lack of social protection, exposure to occupational health and income risks for subpopulations of informal workers is determined by the specific physical and social environments of their workplaces. Efforts to improve the health of informal workers should consider the contexts in which informal work takes place to develop tailored interventions for subpopulations of informal workers.